Possible pharmacological treatment in study phase for COVID-19 symptomatic patients: An integrative review (Research, Society and Development, 2021)
Objective: To perform an integrative review regarding the possible pharmacologic treatment currently being studied as therapeutics strategy for COVID-19 positive patients. Methods: An integrative review was performed using studies in the Medical Literatura Analysis and Retrieval System database, in the PUBMED search engine, in which were selected 58 articles regarding 9 pharmacological classes. Results: The distribution of the 58 articles included in this review was categorized by approached drug type. Were considered treatment with significant improvement the ones which presented viral load decrease, hospital time decrease or with statistically significant clinical improvement according to the criteria of each publication. Conclusion: Considering the urgency of the rapid production of results, a great difficulty of production of blind and double-blind studies was observed, limiting the scientific community to retrospective and observational studies, mostly, which are not as efficient as the mentioned before. Based on the studies observation, an efficient treatment to COVID-19 is not yet available, making the execution of preventive measures crucial, in order to avoid the impact of the disease in the population.